1ISG-013 Budget impact analysis of lung cancer immunotherapy: a hospital perspective. (March 2019) - Pierobon, E; Capano, F; Ielo, D
Abstract : Background: The evaluation of the economic impact of therapies has become mandatory to guarantee sustainability to the health service, since neoplasms have assumed considerable economic burden in developed countries: 42% of the expenditure for high-cost therapies is for the most common pathologies, including lung. Purpose: To estimate a hypothesis of future expenditure for the immunotherapy in second-line treatment of non-small cell lung cancer (NSCLC), through a budget impact analysis. Material and methods: The analysis was carried out adopting a time horizon of 13 months, the hospital's perspective and considering only direct costs of drugs' purchase. The population corresponds to patients with a diagnosis of NSCLC, eligible for second-line immunotherapy. The model used was defined based on real clinical data: patients actually treated were selected from August 2017 to August 2018, a period in which both nivolumab and pembrolizumab were available in the hospital. The annual cost of therapy was calculated based on the milligrams of drug consumed, (thus considering the drop-in and drop-out rate) and the price of the drug according to the regional public tender. To calculate the drop-in and drop-out rate for atezolizumab, reference was made on overall survival data of the pivotal trial. Therefore, three theoretical scenarios were considered: without introduction into therapy of atezolizumab (first); all naive patients received atezolizumab (second); and 50% of the naive received pembrolizumab and 50% atezolizumab (third). Results: In the first scenario, the initial distribution of patients treated with pembrolizumab compared to nivolumab is 3 vs 17 (month 1), to reach 28 vs 24 (month 13), and the consequential cumulative costs are (€1, 131, 240 and €1, 481, 196 respectively), for a total of €2, 612, 435. In the second scenario the cumulative costs are €2 72 526 for pembrolizumab, €6 23 831 for nivolumab and €1, 692, 250 for atezolizumab, (total of €2, 588, 607, +0.9% compared with the first), while in the third scenario the costs are €1, 804, 842, €6 23 831 and €8 50 406 respectively for a total of €3, 279, 079 (+20% compared to the second). Conclusion: Based on our setting, costs are comparable in the three scenarios even if the cost per administration is almost double for pembrolizumab compared with atezolizumab. One main limitation of the study is that, in the near future, new indications and new therapies may be approved. References and/or acknowledgements: Conflict of interest. Corporate-sponsored research or other substantive relationships; advisory board with grant for novartis, sanofy, maya idee; and telephone interview with honoraria for doxafarma, participation in courses and conferences sponsored by various pharmaceutical companies.